(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the disinfestation, in vitro propagation and subculture of ora-pro-nóbis. In the first experiment, the explants were disinfested with different concentrations of sodium hypochlorite (2%, 4%, 6%). In the second, 600 nodal segments were propagated under different concentrations of MS medium (MS, MS/2, MS/4) and combinations of phytoregulators: 1) ANA (0.5μM) + BAP (0.5μM); 2) ANA (0.5μM) + BAP (1.0μM); 3) ANA (0.5μM) + BAP (1.5μM); 4) ANA (0.5μM) + BAP (2.0μM); 5) ANA (0.5μM), with and without addition of activated carbon. In the third, subculture was carried out in MS medium from the calluses developed in the second experiment, submitted to three treatments: T1 - ANA (2μM) + BAP (4μM); T2 - ANA (0.1μM) + BAP (1μM) and T3 - ANA (0.5μM). The concentration of 4% of NaClO was more efficient, presenting 5% of contamination. The highest callus multiplication rates were observed in MS/2 medium without addition of charcoal, supplemented with 0.5μM of ANA and different concentrations of BAP (1.0μM, 1.5μM and 2.0μM) with means of 0.85 and 0.80 callus per treatment. In 47.16% of the explants there was fungal and bacterial contamination and 23.5% oxidation. There is a need to develop protocols for the establishment of ora-pro-nóbis in vitro as, for example, alternatives to control oxidation, contamination and adequate concentrations of growth regulators.